Chaotic ant swarm optimization to economic dispatch / Mohd Syafiq Md Salleh - Md Salleh, Mohd Syafiq (2010)
Economic Dispatch (ED) solution for a power system gives the optimal combination of power output for all the generating cost in order to minimize total fuel cost while satisfying the load demand and operational constraint. Based on the chaotic system theory, this paper presents a Chaotic Ant Swarm Optimization (CASO) to solve ED problems. To evaluate the proposed method, a three unit generating power system was tested in order to obtain the minimum cost of generator. Chaotic Ant Swarm optimization (CASO) algorithm used in this study was implemented by using MATLAB 7.5.0 (R2007b). Results demonstrate that the method can obtain feasible and effective solution.